QAULAN LAYYINA FOR LEADERS: IN TAFSIR MAFATIH AL-GHAYB - Zulfahmi Zulfahmi (Proceeding International Seminar of Islamic Studies, 2022)
Qaulan Layyina is one of the methods of da'wah, because the main purpose of da'wah is to invite others to the truth, not to force and show strength. The event illustrates the need to strengthen da'wah so that the work of da'wah is strong and strong especially when the da'wah partners who will be faced are difficult to invite to the truth, such as leaders who are beautiful, communities that tend to be despicable and so on. Thus, Qaulan Layyina became one of the alternatives to be able to realize a proselytizing full of peace that does not have to end in violence, because the approach used is a meek word. One of the Islamic mufassir who focused on making it a part was Fakhruddin Al-Razi in his monumental work, the book of Tafsir Mafatih Al-Ghayb.Keywords: Qaulan Layyina, Leader, Tafsir Mafatih Al-Ghayb